PENGARUH TUNNELING INCENTIVE DAN INTANGIBLE ASSETS TERHADAP TRANSFER PRICING DENGAN TAX MINIMIZATION SEBAGAI VARIABEL MODERASI - Hanna, Riska; Ratnasari, Fina (JURNAL AKUNTANSI BARELANG, 2025)
The purpose of this research is to determine the effect of Tunneling Incentives and Intangible Assets on Transfer Pricing with Tax Minimization as a moderating variable. This study uses a sample of Non-Cyclical Consumer Sector Companies listed on the Indonesia Stock Exchange from 2019 to 2023. By utilizing financial statements and purposive sampling techniques, 9 companies were selected from a population of 125 in the Non-Cyclical Consumer Sector. A total of 45 data observations were obtained over five years. The analysis was conducted using Eviews version 13. The findings reveal that, although Tunneling Incentives no have affect transfer pricing, intangible assets have influence transfer pricing, tax minimization can moderate the effect of intangible assets, and tunneling incentives do not moderate transfer pricing.